Viral Vectors for Gene-Directed Enzyme Prodrug Therapy - Schepelmann, Silke; Springer, Caroline J. (Current Gene Therapy, 2006)
Conventional cancer treatments are often hampered by a lack of tumour selectivity, resulting in toxicity to healthy tissue. Gene-directed enzyme prodrug therapy (GDEPT) is a suicide gene therapy approach that aims to improve the selectivity of chemotherapy by enabling cancer cells to convert non-cytotoxic prodrugs to cytotoxic drugs. Many enzyme/ prodrug systems have been described, some of which have already been tested in clinical trials. A key component of GDEPT is a foreign enzyme that is expressed selectively at the tumour site where it converts the prodrug into the cytotoxic agent. The gene encoding the prodrug-activating enzyme needs to be expressed selectively and efficiently in tumour cells in order to spare normal tissue from damage. Substantial efforts have been made to develop gene therapy vectors that are capable of targeting cancer cells. A large number of gene delivery systems have been described for GDEPT: Viral vectors are the most advanced. They include replication-deficient and replication-selective (oncolytic) viruses. Recent advances in engineering viruses for GDEPT are reviewed in this article and data from both preclinical studies and clinical trials are discussed.
Keywords: chemotherapy